Oral memorization methods (Journal of the College of Basic Education, 2023)
Folk songs and religious or secular lyrical material were transmitted from one era to another by the fathers.to the children through oral memorization. This method is considered the basis for memorizing the heritage material.in the chests of the sons of the same community. Among the drawbacks of this method is its abilityWeak in achieving proper memorization of the subject to be memorized, due to the teacher’s weakness in the first place.Memorizing that material (a song, a hymn...) or the recipient’s weakness in terms of distinguishing melodic tracksdelivered by the teacher, as well as the divergence and mastery of the variable on that subject from a teacherto another and from one recipient to a second recipient (according to the ability and talent of each person), which leads in somesometimes due to the divergence of the original melodic paths and the implicit change, and sometimes a changecompletely of the lyrical material, especially if that material is from the heritage that is not recorded or recorded (notretained) which consequently leads to the loss of the basic melody or its alteration intentionally or withoutIntentionally, hence the researcher considered the justification for his research after sensing the loss and change of quite a fewOld traditional songs and chants about their original melodic path through the history of their transmission from generationto a generation by means of oral memorization for people who are not originally specialized in the field of music and singingOr to some specialists who tried to add their ideas, taste and personal knowledge in dealingwith the tunes of those materials and thus distorted them instead of transferring them in their original form without intending to thinkSome of them are renewing those lyrical materials that were not originally preserved before (before the appearance ofaudio recording equipment).